2009
DOI: 10.1121/1.3081385
|View full text |Cite
|
Sign up to set email alerts
|

A micro-machined source transducer for a parametric array in air

Abstract: Parametric array applications in air, such as highly directional parametric loudspeaker systems, usually rely on large radiators to generate the high-intensity primary beams required for nonlinear interactions. However, a conventional transducer, as a primary wave projector, requires a great deal of electrical power because its electroacoustic efficiency is very low due to the large characteristic mechanical impedance in air. The feasibility of a micro-machined ultrasonic transducer as an efficient finite-ampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Taking into account the stress distribution in the radial direction, the piezoelectric layer was designed to be smaller than the diaphragm because electro-mechanical coupling is more effective when the piezoelectric layer covers a smaller area in the center of the diaphragm rather than the total area of the circular plate. [18][19][20] The main design parameters of the sensor discussed here are the silicon diaphragm radius r s , the thickness t s , the piezoelectric layer radius r p and thickness t p , and the backing chamber dimensions. The front of the diaphragm is exposed to the external medium through the housing, and the chamber is located on the opposite side of the diaphragm.…”
Section: Flexural Thin Plate With a Piezoelectric Layermentioning
confidence: 99%
“…Taking into account the stress distribution in the radial direction, the piezoelectric layer was designed to be smaller than the diaphragm because electro-mechanical coupling is more effective when the piezoelectric layer covers a smaller area in the center of the diaphragm rather than the total area of the circular plate. [18][19][20] The main design parameters of the sensor discussed here are the silicon diaphragm radius r s , the thickness t s , the piezoelectric layer radius r p and thickness t p , and the backing chamber dimensions. The front of the diaphragm is exposed to the external medium through the housing, and the chamber is located on the opposite side of the diaphragm.…”
Section: Flexural Thin Plate With a Piezoelectric Layermentioning
confidence: 99%
“…With ultrasonic ranging sensors, electrical beam steering may enable ar eduction in the number of sensors required for navigational control of as ystem of mobile robots. The parametric array (PA) ultrasonic ranging sensor [1] has high spatial resolution due to its narrowbeam width; however, alarge number of these sensors are required to covern avigation overag iven angular region compared with ultrasonic sensors with awider beam width, which may increase the cost of the navigation system. Forthese reasons, electrical beam steering is particularly desirable with PA ultrasonic ranging systems.…”
Section: Introductionmentioning
confidence: 99%
“…Using this technique, the aperture of the source can be small compared with the wavelength of the generated sound [2]. The high directivity of the lower DFW generated by the PA makes it suitable for applications such as underwater sound navigation systems (SONAR) [ 3], high-resolution ultrasonic ranging acoustic navigation systems for mobile robots [1,4], and PA loudspeaker systems [5,6]. However, since aP Ae xploits anonlinear phenomenon, the suitability of electrical beam steering methods based on linear acoustics requires careful investigation.…”
Section: Introductionmentioning
confidence: 99%
“…In another ZnO work, Lee and Lee [18] reported an actuation response of 77 nm at a resonance of 54.8 kHz and 1 V pk for a circular microphone which is 2 mm in diameter. Lee et al [19] designed an array of circular diaphragms with a central PZT embossment for an ultrasonic ranging system using the parametric array effect. The authors reported two diaphragm designs with diameters of 1.2 and 1.42 mm and a thickness of 15 μm.…”
mentioning
confidence: 99%